1997
DOI: 10.1093/emboj/16.17.5273
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor C/EBP-beta and its role in ovarian function; evidence for direct involvement in the ovulatory process

Abstract: Gonadotropins are responsible for maturation of the ovarian follicle and the oocyte. Ovulation is the ultimate step in this process and involves disintegration of the follicular wall and subsequent release of an oocyte into the oviduct. These events are triggered by a surge of luteinizing hormone (LH). Genes expressed in the ovary, that respond to LH, are likely to be involved in the biochemical pathways that regulate ovulation. The transcription factor C/EBP-beta is induced promptly in the ovary, as a respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…It has also been shown to transactivate the c-fos serum response element upon activation of the Ras-dependent signaling pathway in response to mitogenic stimulation (31). C/EBP␤ is found to be constitutively expressed in the liver, intestine, lung, adipose tissue, spleen, and kidney (39 -43) and plays an important role in adipocyte (40,44), hepatocyte (45), and mammary gland differentiation (29), as well as in ovulation (32,46). C/EBP␤ knock-out mice (43) have alteration in glucose homeostasis (47), immunological defects (48), develop lymphoproliferative disorders (49,50) and defects in female reproduction and infertility (32).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown to transactivate the c-fos serum response element upon activation of the Ras-dependent signaling pathway in response to mitogenic stimulation (31). C/EBP␤ is found to be constitutively expressed in the liver, intestine, lung, adipose tissue, spleen, and kidney (39 -43) and plays an important role in adipocyte (40,44), hepatocyte (45), and mammary gland differentiation (29), as well as in ovulation (32,46). C/EBP␤ knock-out mice (43) have alteration in glucose homeostasis (47), immunological defects (48), develop lymphoproliferative disorders (49,50) and defects in female reproduction and infertility (32).…”
Section: Discussionmentioning
confidence: 99%
“…C/EBP␤ plays a key role during differentiation of a number of cell types, including adipocytes (9 -11), hepatocytes (12), and cells of the hematopoietic system (13,14). C/EBP␤ also plays a role in mammary gland development (15) and in ovulation (16,17). C/EBP␤ has been shown to localize in areas of pericentric heterochromatin in 3T3-F442A predipocytes upon GH treatment, as well as during the induction of adipocyte differentiation of 3T3-F442A 2 and 3T3-L1 cells (22).…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal half of LAP contains the transactivation domain, whereas LIP lacks this transactivation domain and acts as an inhibitor of transcription (8). C/EBP␤ plays an important role during differentiation of a number of cell types (9 -14), and is also implicated in mammary gland development (15) and in ovulation (16,17). The participation of C/EBP␤ in a wide variety of physiological events suggests that multiple features of its regulation may contribute to diverse biological outcomes.…”
mentioning
confidence: 99%
“…If truly so, C/EBP␣ should be considered as potential substitute for C/EBP␤ in the C/EBP␤-deficient mouse ovary (60 -63). It has been shown that the ovaries of the latter null mice do not ovulate (60,64) despite normal production of gonadal steroids and expression of steroidogenic enzymes, probably including StAR. 3 Like C/EBP␤, GATA-4 had not been described previously as a potential regulator of genes encoding steroidogenic enzymes, or their accessory proteins.…”
Section: Fig 10mentioning
confidence: 99%